Combined Effect of Factor V Leiden and Prothrombin 20210A on the Risk of Venous Thromboembolism - Emmerich, Joseph; Rosendaal, Frits R.; Cattaneo, Marco; Margaglione, Maurizio; De Stefano, Valerio; Cumming, Tony; Arruda, Valder; Hillarp, Andreas; Reny, Jean-Luc; the study group for pooled-analysis in venous thromboembolism (Thrombosis and Haemostasis, 2001)
Factor V Leiden and factor II G20210A mutations are two frequent genetic risk factors involved in venous thromboembolism (VTE). The goal of this pooled analysis of 8 case-control studies, comprising a total of 2310 cases and 3204 controls, was to precisely estimate the risk of VTE in patients bearing both mutations (double heterozygotes). Odds ratios for VTE were 4.9 (95% CI; 4.1-5.9) for the factor V Leiden and 3.8 (3.0-4.9) for the factor II G20210A mutation. Fifty-one cases (2.2%) and none of the controls were double heterozygotes. The odds ratio for venous thrombosis in double heterozygotes was 20.0 (11.1-36.1). Twelve percent of patients heterozygous for factor V Leiden were also heterozygous for factor II G20210A and conversely 23% of patients heterozygous for factor II G20210A were also heterozygous for factor V Leiden. Furthermore, in this large population we analyzed the effect of oral contraceptive (OC) in women carrying one of these mutations. Odds ratio for VTE associated with OC was 2.29 (1.72-3.04). In factor V Leiden carriers using OC, the odds ratio for VTE was 10.25 (5.69-18.45). The odds ratio of the association of factor II mutation and OC use was 7.14 (3.39-15.04). Finally, we also confirmed that the frequency of factor V Leiden was lower in patients with pulmonary embolism than in patients with deep vein thrombosis without PE (odds ratio 0.69). Conversely, factor II G20210A mutation was equally balanced in both patient groups.
Keywords: Factor V Leiden; factor II G20210A; deep vein thrombosis; oral contraceptive